2021
DOI: 10.17711/sm.0185-3325.2021.021
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies associated to widespread fear and post-traumatic stress criteria in a Mexican sample during COVID-19 pandemic: A cross-sectional study

Abstract: Introduction. The COVID-19 pandemic has impacted the population generating widespread fear due to people’s perception that both their health and safety are at risk. Widespread fear, a synonym for social anxiety, is associated with affective intrusive cognitions. Likewise, it is related to symptoms of post-traumatic stress, physiological intrusive and eluding coping responses, and could be associated with long-term vulnerability to develop PTSD. Objective. To assess the association between coping strategies, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In the first study, the participants who dropped out of the intervention were invited to respond to the SUS, along with ad hoc instruments designed to allow us to analyze the participants' reasons for abandoning the intervention. The study was conducted using 3 psychological intervention platforms that were available during the COVID-19 pandemic: Salud Mental COVID-19 [57], Duelo COVID-19 [33], and Personal COVID-19 [58]. In addition, we conducted a qualitative study with the Grief COVID participants to gather information about their perceptions of the intervention.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In the first study, the participants who dropped out of the intervention were invited to respond to the SUS, along with ad hoc instruments designed to allow us to analyze the participants' reasons for abandoning the intervention. The study was conducted using 3 psychological intervention platforms that were available during the COVID-19 pandemic: Salud Mental COVID-19 [57], Duelo COVID-19 [33], and Personal COVID-19 [58]. In addition, we conducted a qualitative study with the Grief COVID participants to gather information about their perceptions of the intervention.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In the same line, in the study of Santomauro et al ( 2 ), published in The Lancet with data of 204 countries and territories during the pandemic of COVID-19, the authors indicated that there was an increase of 53.2 million more cases of major depression, and additionally, 76.2 million cases of anxiety disorders. Regarding Latin America, before the pandemic the mental disorders were perceived as common ( 3 ), and during the pandemic the available scientific literature indicates that the population of Latin American countries exhibited an increase in symptoms of anxiety ( 4 ), depression ( 5 ), post-traumatic stress disorder ( 6 ), sleep problems ( 7 ), and alcohol consumption ( 8 ), among other problems.…”
Section: Introductionmentioning
confidence: 99%